Towards the Description of the Genome Catalogue of Pseudomonas sp. Strain M1 - Soares-Castro, Pedro (American Society for Microbiology, 2013)
Pseudomonas sp. strain M1 is a soil isolate with remarkable biotechnological potential. The genome of Pseudomonas sp. M1 was sequenced using both 454 and Illumina technologies. A customized genome assembly pipeline was used to reconstruct its genome sequence to a single scaffold.